"It's Easy to Put Oneself in the Shoes of Others." Results of a School Study in Geography Lessons on Working with Authentic Personal Narratives in Comparison to Factual Texts - Astrid Lütje; Alexandra Budke (MDPI AG, 2023)
Texts represent the most frequently used medium in geography teaching, although they do not belong to leading subject-specific media. Despite their undisputed didactic importance, they have not yet been sufficiently researched. In this article, we consider the use of authentic and personal narratives in geography lessons. We first show their theoretical potential for realistic, multi-perspective and motivating teaching. Then, we present a school study in which the use of authentic, personal narratives was investigated in comparison to a factual text. The areas of investigation were the students' understanding of the content of a geographical topic, their memory performance and their motivation to work. The results show that authentic, personal narratives are better suited than factual texts to convey a topic to pupils in a multi-perspective and differentiated way. They also confirm their potential to empathise better with other people and to understand their actions through changes in perspective. Regarding recall performance, however, the results show no difference between the two groups. Finally, the results of the school study are considered in the context of forming suggestions for the use of authentic, personal narratives in geography lessons.